The membrane-associated ubiquitin ligase MARCHF8 degrades MHC-I in HPV-positive head and neck cancer for immune evasion - Mohamed I. Khalil; Jie Wang; Lexi Vu; Canchai Yang; Congcong Yin; Smriti Chadha; Harrison Nabors; Daniel Vocelle; Danielle G. May; Rachel J. Chrisopulos; Craig C. Welbon; Li Zhou; et al. (Proceedings of the National Academy of Sciences, 2026)
The loss of major histocompatibility complex class I (MHC-I) molecules has been proposed as a mechanism for cancer immune evasion. Nevertheless, the mechanism is poorly understood. We report here that membrane-associated RING-CH-type finger 8 (MARCHF8), upregulated by human papillomavirus (HPV), ubiquitinates and degrades MHC-I in HPV-positive head and neck cancer (HPV+ HNC). Inhibiting MARCHF8 restores MHC-I levels on HPV+ HNC cells, suppresses tumor growth, and increases the infiltration of natural killer (NK) and T cells in the tumor microenvironment. Furthermore, Marchf8 knockout markedly increases cross talk between cytotoxic NK cells and CD8 + T cells with macrophages and enhances the tumor-killing activity of CD8 + T cells. Interestingly, Marchf8 knockout, in combination with anti-PD-1 treatment, further enhances tumor suppression and increases NK and T cell infiltration in mice bearing immune checkpoint inhibitor–refractory tumors. Our findings suggest that MARCHF8 could be a promising target for immunotherapy for HPV+ HNC patients.